Pemanfaatan Website Sebagai Media Informasi Serta Meningkatkan Branding Apotek Assyifa Farma - Risma Risma; Tiara Dwi Andriansyah; Sularno Sularno; Zulfitri Yani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The use of information technology has become an essential strategy to enhance business competitiveness, including in the healthcare service sector. This study aims to analyze the role of websites as an information medium and a branding tool for Apotek Assyifa Farma. The research method used is descriptive qualitative with data collected through observation, interviews, and documentation. The results show that the existence of a website helps expand the reach of information to customers, facilitates service access, and improves the pharmacy’s professional image in the community. In addition, the informative design and content of the website strengthen brand identity and customer trust. Therefore, optimizing website utilization can serve as an effective medium to support communication and branding strategies of Apotek Assyifa Farma in the digital era.